2013
DOI: 10.1371/journal.pone.0070955
|View full text |Cite
|
Sign up to set email alerts
|

Red and Processed Meat Intake Is Associated with Higher Gastric Cancer Risk: A Meta-Analysis of Epidemiological Observational Studies

Abstract: BackgroundRed and processed meat was concluded as a limited-suggestive risk factor of gastric cancer by the World Cancer Research Fund. However, recent epidemiological studies have yielded inconclusive results.MethodsWe searched Medline, EMBASE, and the Cochrane Library from their inception to April 2013 for both cohort and case-control studies which assessed the association between red and/or processed meat intake and gastric cancer risk. Study-specific relative risk estimates were polled by random-effect or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(71 citation statements)
references
References 62 publications
(126 reference statements)
3
66
0
2
Order By: Relevance
“…The subjects who preferred very salty food in diet had a more than 30-fold risk, compared to those preferring to non-salty food, which was in agreement with previous studies reporting that salt was a risk factor for gastric cancer (Nazario et al, 1993;Ramon et al, 1993;Tsugane et al, 2004). Although there was inconsistency regarding results of the association between salted meat and gastric cancer in literatures (Sjödahl et al, 2008;Keszei et al, 2012;Van Den Brandt et al, 2013), recent reviews summarized that increased consumption of processed meat including salted meat was significantly associated with gastric cancer Zhu et al, 2013). Another study conducted in a high risk area of gastric cancer in northwest of China also suggested long-term exposure to salted pork might result in repeated gastric mucosal damage and repair, and finally in severe dysplasia and malignancy (Yuan et al, 1996).…”
Section: Discussionsupporting
confidence: 75%
“…The subjects who preferred very salty food in diet had a more than 30-fold risk, compared to those preferring to non-salty food, which was in agreement with previous studies reporting that salt was a risk factor for gastric cancer (Nazario et al, 1993;Ramon et al, 1993;Tsugane et al, 2004). Although there was inconsistency regarding results of the association between salted meat and gastric cancer in literatures (Sjödahl et al, 2008;Keszei et al, 2012;Van Den Brandt et al, 2013), recent reviews summarized that increased consumption of processed meat including salted meat was significantly associated with gastric cancer Zhu et al, 2013). Another study conducted in a high risk area of gastric cancer in northwest of China also suggested long-term exposure to salted pork might result in repeated gastric mucosal damage and repair, and finally in severe dysplasia and malignancy (Yuan et al, 1996).…”
Section: Discussionsupporting
confidence: 75%
“…Certain varieties of meat that can reduce (fish and seafood) or increase (luncheon meat) the risk for certain types of cancers were not among the study aims of this analysis, and so their consumption was not taken into consideration. This aspect was made clear to the patients during the interview [19,20]. Consumption was understood as the habitual intake during the majority of the individual's lifetime.…”
Section: Methodsmentioning
confidence: 99%
“…A high salt intake has been identified as a risk factor for gastric cancer in case‐control studies 5. Red and processed meat intake was associated with a 43% increase in the risk for gastric cancer 6. Epstein‐Barr virus‐encoded small RNA has been detected in up to 17.9% of patients with gastric cancer 7…”
Section: Risk Factors For Gastric/gej Cancersmentioning
confidence: 99%